The Reality of Expressive and Receptive Skills among Early Childhood Students from the Point of View of Teachers and supervisors and Ways to develop it - Al-Dweish, Ashwaq Aloush; Hejr, Amna'ah (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed to investigate the current state of expressive and receptive language skills among early childhood students, identify related challenges, and propose strategies for their development from the perspective of teachers and educational supervisors. The research adopted a descriptive analytical survey approach and utilized a 47-item questionnaire, structured across three main themes. This instrument was administered to a cluster random sample comprising 50 teachers and 20 supervisors from the Cordoba Education Department in Riyadh. The findings revealed a moderate level of agreement (64.2%) among teachers and educational supervisors regarding the expressive skills of early childhood students, and a similar moderate agreement (63.8%) concerning their receptive skills. Furthermore, there was moderate agreement on the challenges associated with expressive skills (66.4%) and receptive skills (67.3%). Significantly, the study found a very high level of agreement (84.2%) on proposed developmental strategies for expressive skills and an equally high agreement (85%) for receptive skills among early childhood students. In light of these results, the study recommends a strong emphasis on the early childhood stage and the cultivation of children's linguistic and receptive skills during this critical period. This can be achieved through a variety of developmental proposals, including offering individual and group activities designed to enhance their expressive and receptive language abilities, leveraging educational resources, and providing a safe and nurturing environment conducive to skill development.
Keywords: Language Skills; Pre-school Stage